Wear and friction performance under lubricated reciprocating tests of steel powder mixtures sintered by Spark Plasma Sintering. (May 2018) - Boidi, G.; Fukumasu, N.K.; Machado, I.F.
Abstract: Literature indicates that porosity in sintered materials decreases mechanical properties and fatigue resistance. However, given porosity shape and distribution on a surface, it is possible that these small cavities could improve surface lubrication conditions. This work aims to evaluate the effects of porosity, surface finishing, oil viscosity and heat treatment on wear and friction of two sintered carbon steels during lubricated high contact pressure tests. Samples were characterized prior and after tests by SEM, optical profilometry and hardness measurements. Main results showed that surface hardness and porosity controlled wear behavior of sintered material in high load conditions. Rougher material seemed to activate anti-wear additives contained on the lubricant, promoting less worn volume than polished samples. Highlights: Tribological performance of FeCCr and FeCMo mixtures sintered by SPS. Apparent surface hardness and surface porosity controlled wear behavior. High porosity caused large deformation, pores closure and higher worn volume. Extreme pressure additives seemed to activate on rougher surfaces reducing wear.